THE INFLUENCE OF EVENT SPONSORSHIP, BRAND AMBASSADOR AND BRAND EXPOSURE IN MAINTAINING BRAND IMAGE (Case Study of Wardah Cosmetic Products Among Female Students of Universitas Malikussaleh) - Nisa Humaira; Hamdiah; Jullimursyida; Khairina AR (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to assess the influence of event sponsorship (X1), brand ambassadors (X2), and brand exposure (X3) on the brand image (Y) of Wardah cosmetic products among female students at Malikussaleh University. The sampling method used was purposive sampling, with a total of 104 respondents. Primary data was collected through questionnaires. The data analysis techniques employed include multiple linear regression analysis, classical assumption tests, instrument tests (validity and reliability), determination tests (R2), and hypothesis testing (T) using SPSS 25 software. The results indicate that, partially, event sponsorship has a positive and significant effect on brand image, brand ambassador does not have a significant effect on brand image, and brand exposure has a positive and significant effect on brand image.